APLIKASI EDIBLE COATING BIONANOKOMPOSIT UNTUK PRODUK PEMPEK PADA PENYIMPANAN SUHU RUANG - Mona Nur Moulia; Rizal Syarief; Nugraha Edhi Suyatma; Evi Savitri Iriani; Harsi Dewantari Kusumaningrum (Jurnal Teknologi dan Industri Pangan, 2019)
Edible packaging is a relatively new technology for food preservation, many research on edible coat-ing had been conducted and it proved to prolong storage life and to improve the quality of food products. The main objective of this research was to investigate the shelf-life of pempek coated with edible bionanocomposite made from cassava starch, zinc oxide nanoparticles (ZnO-NPs) and garlic extract. Bionanocomposite edible coating Z3B20 (containing ZnO-NPs 3% and garlic extract 20%) and Z3B30 (ZnO-NPs 3% and garlic extract 20%) were applied on pempek products. The parameters observed were total microbes, total Staphylococcus aureus, texture, total volatile nitrogen (TVN), moisture content, pH during storage at room temperature for 0, 6, 24 and 48 hours. The results showed that the total microbe numbers increased during the storage. Pempek coated with Z3B20 has a total microbes of 6.00 log CFU/g which was lower than that of control (6.99 log CFU/g). Meanwhile pempek coated with Z3B30 has Staphylococcus aureus counts of 2.93 log CFU/g which was lower than the control (4.05 log CFU/g) and pempek coated with Z3B30 stored for 48 hours (3.64 log CFU/g). The TVN values increased during storage from 17.33 mg/100 g to 18.94 mg/100 g while those in Z2B30 and Z3B30 decreased to 14.80 mg/100 g in Z3B30, respectively. The hardness increased during storage from 9.93 N in control, to 10.01 N in Z2B30 and 13.15 N in Z3B30, respectively. All coated pempeks after storage up to 48 hours had higher moisture contents. On the other hand, the pHs decreased for all samples during storage. Based on the total microbe numbers and TVN values, it can be concluded that the coated pempek stored for 24-hour or less were acceptable for consumption.